Proses Kreatif Ubiet dalam Mengembangkan Puisi Senja di Pelabuhan Kecil - Mirna Nurmala; Yanti Heriyawati; Indra Ridwan (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
Senja di Pelabuhan Kecil is a poem by Chairil Anwar which was later made into a song by Nya Ina Raseuki who is familiarly called Ubiet. Ubiet is known as a music composer who is unique in terms of musical ideas and vocal ornamentation, one of which is on the song of Senja di Pelabuhan Kecil. This can be seen from the character of the song which has a different style from other musicians adopting Chairil Anwar's poem. This research study focuses on how the creative process carried out by Ubiet in making the song Senja di Pelabuhan Kecil. The process is starting from the stage of developing ideas, transforming works of art, to becoming complete expressions and works of music. The research was conducted using qualitative methods with data collection techniques such as; observation, interview, documentation, and literature study. The writer uses Mel Rhodes' theory of creativity as a tool to examine the object of the problem taken in writing this study. The Rhodes creativity concept discusses four points, namely; press, person, process, and product or what is known as the 4p concept. This research focuses the discussion on the process point. The analysis method is supported by the approach of the principles of musical poetry according to Hamdy Salad. The results of this study are targeted to find a variety of new musical expressions from the concept of musical poetry and as a musical product with the concept of contemporary keroncong.Keywords: Creative Process, Ubiet, Poetry, Senja di Pelabuhan Kecil